Oral health and impact on performance of athletes participating in the London 2012 Olympic Games: a cross-sectional study - Needleman, I.; Ashley, P.; Petrie, A.; Fortune, F.; Turner, W.; Jones, Niggli, J.; Engebretsen, L.; Budgett, R.; Donos, R.; Cough, T.; Porter, S. (British Journal of Sports Medicine, 2013)
Background: Oral health is important both for well-being and successful elite sporting performance. Reports from Olympic Games have found significant treatment needs; however, few studies have examined oral health directly. The aim of this study was to evaluate oral health, the determinants of oral health and the effect of oral health on well-being, training and performance of athletes participating in the London 2012 Games.